KNOWLEDGE MANAGEMENT BASED ORGANIZATIONS - Manev, Gjorgji; Jakimovski, Jorde (International Journal of Economic Practice and Policy, 2015)
Accomplishment of the goals set by a business organization implies implementation of knowledge management. It allows coordination of the working processes with the information technologies, with a view to adapting the organization’s operations to the problems encountered. Overcoming these problems involves designing and implementation of complex business systems supported by information technology. This can be achieved by management that will monitor the business processes through clear indicators, with the purpose of accomplishing the preset strategic goals. This managerial staff must be fully devoted and committed to their work, to learning and creation of expertise that will help overcome the competition challenges.